Trees in Your Life - Martha C. Monroe (EDIS)
This document explores the diverse ways trees contribute to everyday products beyond paper and lumber. It highlights the role of trees in producing food items like fruits, nuts, and maple syrup, as well as non-food products such as paper, rayon, and cellulose-based items. The publication also discusses the extraction and use of tree-derived chemicals in various industries, emphasizing the importance of trees in maintaining a sustainable lifestyle and their potential to replace petroleum-based products. Published: October 2000.